Republic of Korea : Financial System Stability Assessment and Press Release for the Republic of Korea. (IMF Staff Country Reports; Country Report ;, 2020)
This paper presents Financial System Stability Assessment (FSSA) with the Republic of Korea. The Korean authorities have continued their efforts at upgrading the prudential, legal, and supervisory framework for the financial sector, and keeping up with international standards and practices in other G20 jurisdictions. The authorities have been strengthening the system with micro and macroprudential measures against vulnerabilities, strengthening the crisis management framework, and upgrading the prudential and legal framework. The FSSA suggests moving toward a more forward-looking monitoring and systemic risk identification mechanism. The reliability of various stress tests could be augmented with advanced methods, system-wide monitoring, and testing the overall leverage related to residential properties, households' resilience to adverse shocks, and sovereign contingent liabilities. Stronger focus is required on systemic risks emanating from securities market activities that can amplify contagion, including sudden redemption and liquidity pressures in the funds and asset management industry.